2018
DOI: 10.3390/ijms19030869
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Multiple Cytokine Combinations and TGF-β on Differentiation and Functions of Myeloid-Derived Suppressor Cells

Abstract: Myeloid-derived suppressor cells (MDSCs) regulate T cell immunity, and this population is a new therapeutic target for immune regulation. A previous study showed that transforming growth factor-β (TGF-β) is involved in controlling MDSC differentiation and immunoregulatory function in vivo. However, the direct effect of TGF-β on MDSCs with various cytokines has not previously been tested. Thus, we examined the effect of various cytokine combinations with TGF-β on MDSCs derived from bone marrow cells. The data s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 67 publications
(49 citation statements)
references
References 29 publications
(48 reference statements)
1
48
0
Order By: Relevance
“…Lee et al have found Treg-derived TGF-β could e ciently promote MDSC proliferation and function in murine colitis (47). A recent study also reported that TGF-β could increase the expansion of MDSCs and enhance the suppressive capacity of MDSCs in vitro (48). Similarly, in our experiment, the canonical signaling of TGF-β was activated, the phosphorylation of Smad2 and Smad3 was strikingly enhanced in MDSCs cocultured with BM-MSCs.…”
Section: Discussionsupporting
confidence: 78%
“…Lee et al have found Treg-derived TGF-β could e ciently promote MDSC proliferation and function in murine colitis (47). A recent study also reported that TGF-β could increase the expansion of MDSCs and enhance the suppressive capacity of MDSCs in vitro (48). Similarly, in our experiment, the canonical signaling of TGF-β was activated, the phosphorylation of Smad2 and Smad3 was strikingly enhanced in MDSCs cocultured with BM-MSCs.…”
Section: Discussionsupporting
confidence: 78%
“…Still little is known about the mechanisms that lead to the increasing of M-MDSC, especially in the microenvironment of leukemia [20] and lymphoma [24]. Lee et al [36] found that TGF-b induced the expansion of the monocytic MDSC population, expression of immunosuppressive molecules by MDSCs, and the ability of MDSCs to suppress CD4+ T cell proliferation. In our study, we found a significantly higher percentage of M-MDSC with intracellular IL-10 or TGF-b expression in CLL patients than in healthy volunteers.…”
Section: Discussionmentioning
confidence: 99%
“…We also presume that myelosuppression occurring in severe neutropenic patients contributes to improve the prognosis of the patients. Myeloid-derived suppressor cells (MDSCs), which reveal immunosuppressive in tumor microenvironment via inhibition of CD4+ T cell proliferation [ 25 ], accumulate in tumor cells and peripheral blood as the disease is progressed or in advanced stages of pancreatic cancer [ 26 , 27 , 28 , 29 , 30 ]. Reducing the number of MDSCs is a key antitumor mechanisms of some chemotherapy agents, including 5-FU [ 31 ], which prevents the accumulation of MDSCs in patients with pancreatic cancer [ 32 ].…”
Section: Discussionmentioning
confidence: 99%